The effectiveness of Question Prompt Lists (QPL) in enhancing treatment outcomes for cancer patients among tribal population in Meghalaya: A quasi-experimental design - Redolen Rose Dhar; Bhageerathy Reshmi; Ramesh Holla; Vennila Jaganathan; Kripa Josten; Anisha Mawlong (PLoS ONE, 2025)
Background Cancer remains a leading cause of death worldwide, with a significant burden in India’s northeastern states, including Meghalaya. Patients from tribal communities often face unique sociocultural and communication barriers that affect their engagement in care. Effective patient–physician communication improves satisfaction, adherence, and quality of life. This study aims to assess the consultation satisfaction and effectiveness of a Question Prompt List (QPL) in enhancing patient–physician communication and promoting informed decision-making among cancer patients in a tribal population in Meghalaya, India. Methods A quasi-experimental design was employed involving 60 participants diagnosed with head and neck, gastrointestinal, or respiratory cancers. Participants were assigned to an intervention group that received the QPL and a control group that received standard care. Data on consultation satisfaction and patient feedback were collected across two follow-up sessions. Results The intervention group demonstrated statistically significant improvements in multiple domains of consultation satisfaction, including physicians’ responsiveness, patients’ confidence in asking questions, understanding of disease and treatment plans, and discussions of financial aspects. In contrast, the control group showed no significant change across follow-ups. Patient feedback indicated high levels of agreement regarding the QPL’s usefulness, clarity, and ability to facilitate meaningful communication. Conclusion The QPL significantly enhanced patient satisfaction and engagement, demonstrating its effectiveness as a low-cost, culturally adaptable communication tool for oncology consultations among tribal populations. Integrating QPLs into routine oncology practice could strengthen patient-centred care and reduce communication barriers in underserved regions.